ANALISIS KRITIS HAMBATAN PEDAGOGIS MAHASISWA PPL DALAM PEMBELAJARAN BAHASA INDONESIA DI MADRASAH ALIYAH AT-TA’AWUN - Lailatul Janna; Putriyatul Jamilah; Nisma Nisma; Sofiana Sofiana; Ali Armadi; Heriyanti Heriyanti (KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the pedagogical obstacles faced by students of Field Experience Practice (PPL) Group 70 at PGRI University Sumenep in learning Indonesian at Madrasah Aliyah (MA) At-Ta’awun. As prospective teachers, students are expected to master teaching skills that have been learned through the microteaching course. However, in practice, students encounter various obstacles that affect the effectiveness of teaching and learning activities. The research method used is qualitative with a descriptive approach. Data sources involve PPL students, Adjunct Lecturers (DLB), and students of MA At-Ta’awun, with data collection techniques through interviews, observation, documentation, and note-taking techniques. The results of the study show the presence of internal and external obstacles. Internally, students experience a lack of self-confidence, anxiety in public speaking, and difficulty applying theory to field practice due to limited experience. Externally, challenges arise from students' mindset that prioritizes religious studies over general subjects, as well as limitations in learning media facilities that make the classroom atmosphere tend to be rigid and monotonous. Problem-solving efforts are carried out through intensive guidance with mentor teachers and the implementation of more varied and interactive learning strategies to increase student engagement. This study concludes that although there are technical and facility obstacles, innovation in teaching methods is very crucial to enliven the classroom atmosphere in the pesantren environment.